Evaluation of the In Vitro Antimicrobial Activities of Delphinium roylei: An Insight from Molecular Docking and MD-Simulation Studies - Mir, Wajahat R.; Bhat, Basharat Ahmad; Almilaibary, Abdullah; Asdaq, Syed Mohammed Basheeruddin; Mir, Manzoor Ahmad (Medicinal Chemistry, 2022)
Ethnopharmacological Relevance: The burden of antimicrobial resistance demands a continued search for new antimicrobial drugs. The synthetic drugs used clinically have serious side effects. Natural products or compounds derived from natural sources show diversity in structure and play an essential role in drug discovery and development. Objective: Delphinium roylei is an important medicinal herb of Kashmir Himalaya, India. Traditionally this medicinal plant treats liver infections, skin problems, and chronic lower back pain. The current study evaluates the antimicrobial potential of various extracts by in -vitro and in -silico studies. Methods: Three extracts and 168 bioactive compounds analysed through LC-MS data, with the vast majority of them having therapeutic applications. D. roylei have been screened for the antimicrobial activity against bacteria (Escherichai coli, Streptococcus pneumonia, Haemophilus influenzae, Neisseria mucosa) and fungi (Candida albicans, Candida glabrata, Candida paropsilosis) species through molecular docking using autodock Vina, MD simulation and a broth microdilution method for minimum inhibitory concentration (MIC) evaluation. Results: The extracts and the compounds analyzed through the LC-MS technique of Delphinium roylie showed significant antimicrobial activity. Conclusion: Our study established that the leaf extracts of Delphinium roylei exhibit antimicrobial activity and thus confirm its importance in traditional medicine.
Keywords: antimicrobial